Variabilidade genética e seleção de progênies de Eucalyptus Benthamii maiden et cambage - Costa, Rodolfo Manoel Lemes da [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This work aimed to: ( a ) Study the genetic variability of Eucalyptus benthamii through genetic parameters for quantitative traits to develop strategies for breeding programs ; ( b ) Evaluate the genetic correlation between ages and between traits to determine the best parameter and age to select the superior individuals; and ( c ) Select the superior individuals by Multi - Effects Index. The genetic material used was 34 open pollination progenies of E . benthamii , arranged in three trials by randomized block design , varying the number of progenies, replications, and plants per plot , in Telemaco Borba municipality, PR , Brazil . The trails were measured by three, five , and seven years old for diameter at brea st height, plant height , and wood volume. The genetic parameters w ere estimate d by REML/BLUP procedure . There were significant di fferences (at 1% and 5% probability level ) between the progenies for all evaluated traits. The progenies have show n good performance when compared with literature. The values of coefficients of experimental variation and the coefficient of determination values of plot effects have show n low magnitude values , there was no high influence of the environment on the genetic parameters. The coefficients of g enetic v ariation showed there is genetic variability among progen ies , and then by selection is possible to obtain yield gains. Therefore, we concluded that there is ...

O presente trabalho teve como objetivos: ( a ) Estudar a variabilidade genética de Eucalyptus benthamii por meio dos parâmetros genéticos para caracteres quantitativos para subsidiar estratégias para programas de melhoramento : ( b ) Avaliar as correlações genéticas entre caracteres e entre as diferentes idades com intuito de determinar o melhor parâmetro e idade para se realizar a seleção dos melhores indivíduos e ( c ) Selecionar os indivíduos superiores por meio do método do Índice de Multi - efeitos . O material genético ut ilizado neste trabalho corresponde a 34 progênies de polinização aberta de Eucalyptus benthamii , dispostas em t rês experimentos em b locos casualizados, variando o numero de progênies, número de repetições e número de plantas por parcela , situados em Telêmaco Borba - PR . Os experimentos foram mensurados aos três, cinco e sete anos para os caracteres d iâmetro à altura do peito, a ltura de plantas e v olume de madeira . Os parâmetros genéticos foram estimados por meio do procedimento REML/BLUP. Houve difer enças significativas ( variando em nível de 5% e 1% de probabilida de) entre as progênies para os ...
Keywords: Seleção de plantas - Melhoramento genetico; Eucalipto - Influencia do clima; Genetica florestal; Eucalipto - Seleção; Povoamento florestal; Trees - Development